Interventions for youth homelessness: A systematic review of effectiveness studies. (September 2020) - Morton, Matthew H.; Kugley, Shannon; Epstein, Richard; Farrell, Anne
Highlights: A small number of studies showed reductions in youth homelessness. A few evaluations showed effectiveness in preventing homelessness. Most evaluations measured counseling and short-term well-being outcomes. We need more rigorous evidence on shelter, housing, and outreach models. There is little evidence on program effects for specific subpopulations (e.g., according to race, ethnicity, sexual orientation, or gender identity) or contexts (e.g., rural). Abstract: Objective: This systematic review synthesizes effectiveness evidence on interventions to prevent and address youth homelessness. It was conducted primarily for a United States policy and practice audience but involved an international synthesis of evidence. Method: We conducted an international search that included eleven major academic electronic databases, 13 additional relevant institutional web-based publication databases, and a professional outreach for published and unpublished studies of the effectiveness of programs and practices to prevent or address youth homelessness, in Organisation for Economic Co-operation and Development (OECD) countries. We searched databases for studies published or completed between January 1, 2008 and March 19, 2019, and we also reviewed earlier studies synthesized in a similar past systematic review that ended its search in 2008. The review included experimental and quasi-experimental evaluation studies of youth ages 13–25. We included studies that only used pre-post comparisons and denote lower rigor designs clearly in the synthesis. Results: The search identified 4, 387 potentially relevant unique publications. After screening, 66 publications representing 53 unique studies of 54 different interventions remained and were included in this review. The vast majority (83%) of unique studies were conducted in the U.S. Of the 53 unique studies, 22 (42%) involved some type of randomized evaluation. Many studies involved low rigor designs with weak counterfactuals, small sample sizes, and short follow-up periods. Included studies evaluated a range of interventions, and we grouped these into seven broad categories. The largest evidence base on the effectiveness of interventions relates to counseling and treatment interventions to address mental health or health risk behaviors. Overall, these studies showed promising results, but few included long-term follow-up. A small number of studies demonstrated reductions in occurrence of youth homelessness and housing instability, including some intensive case management and support interventions without direct housing assistance components. The field lacks rigorous evaluative evidence of many of the program models on which communities and governments rely to address youth homelessness (for example, street outreach, transitional living programs, youth shelters, host homes, and rapid rehousing). Evaluative evidence is further lacking on how the effects of interventions vary by subpopulations disproportionately impacted by homelessness. Discussion and conclusion: Policy and community interventions to prevent and end youth homelessness require a robust evidence base to inform decision-making. This systematic review presents an important starting point to inform solutions across a range of intervention areas, and it reveals significant areas in which investments in research and evaluation are urgently needed.